Godsdiensvryheid in die ban van NGB Art 36 – seën of vloek? - Fourie, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The understanding of Art 36 of the NGB creates a problem for Christians in a modern Western democracy. The task of the state in a democracy is not to fight religious idolatry and apostasy. Therefore, already at the end of the nineteenth century Abraham Kuyper campaigned for the abolition of this Article. To him, an honest reading of the text makes it clear that the false religion the state had to fight was Roman Catholicism. This article pleads for a hermeneutical approach to Article 36. It should be understood as a reflection of the theocratic political model that reigned when Guido de Brès formulated the NGB. In the context of a modern democracy with constitutionally guaranteed religious freedom and a judicial state, reinterpreting and making the Article relevant only boils down to “hermeneutical gymnastics” and serves no purpose - it should be treated in a way similar to how we treat many historically-dated material in Scripture.